Predictors of rapid plaque progression: an optical coherence tomography study. (25th November 2020) - Araki, M; Yonetsu, T; Kurihara, O; Nakajima, A; Lee, H; Soeda, T; Minami, Y; Uemura, S; Kakuta, T; Jang, I.K
Abstract: Background: Two patterns of plaque progression have been described: slow linear progression and rapid step-wise progression. The former will cause stable angina when the narrowing reaches a critical threshold, while the latter may lead to acute coronary syndromes or sudden cardiac death. Purpose: The aim of the study was to identify morphologic predictors for rapid plaque progression. Methods: Patients who had OCT imaging during the index procedure and follow-up angiography with a minimum of 6-month interval were selected. Non-culprit lesion was defined as a plaque with a diameter stenosis ≥30% on index angiogram. Lesion progression was defined as the decrease of angiographic minimum lumen diameter ≥0.4 mm at follow-up (mean, 7.1 months). Baseline morphological characteristics of the plaques with rapid progression were evaluated by OCT. In a subgroup with follow-up OCT imaging for plaques with progression, morphological changes from baseline to follow-up were assessed. Results: Among 517 lesions, 50 lesions showed progression. These lesions had a significantly higher prevalence of lipid-rich plaque (76.0% vs. 50.5%), thin-cap fibroatheroma (TCFA) (20.0% vs. 5.8%), layered plaque (60.0% vs. 34.0%), macrophage accumulation (62.0% vs. 42.4%), microvessel (46.0% vs. 29.1%), plaque rupture (12.0% vs. 4.7%), and thrombus (6.0% vs. 1.1%), compared to those without progression. The multivariable analysis identified lipid-rich plaque [odds ratio (OR) 2.17, 95% confidence interval (CI) 1.02–4.62, p=0.045], TCFA (OR 5.85, 95% CI 2.01–17.03, p=0.001), and layered plaque (OR 2.19, 95% CI 1.03–4.17, p=0.040) as predictors of subsequent lesion progression. In a subgroup with follow-up OCT, a new layer was detected in 14/41 (34.1%) plaques. Conclusions: Lipid-rich plaque, TCFA, and layered plaque were predictors of subsequent rapid plaque progression. A new layer, a signature of rapid progression through plaque disruption and healing, was detected in 1/3 of the cases. Funding Acknowledgement: Type of funding source: None